KESULITAN SISWA SEKOLAH DASAR DALAM MEMBEDAKAN ANTARA SUKU DAN AGAMA - Rahmadini, Riris; Siregar, Tasya Azra Zulaikha; Purba, Novi Kristina; Sihotang, Ryan I; Kamila, Nurul; Siregar, Waliyul Maulana (Universitas Negeri Medan, 2024)
Cultural and religious diversity in Indonesia is a reality that cannot be denied. However, the phenomenon of elementary school students not understanding religious and ethnic differences is increasingly common, which can lead to negative impacts such as discrimination, conflict and intolerance. This research aims to analyze the factors that cause elementary school students™ difficulties in differentiating ethnicity and religion, as well as offering efforts to overcome these problems. Keywords: religious tolerance, diversity, elementary school students, intolerance